A loaded technique for modeling oblique wire in finite‐difference time‐domain method. Issue 10 (14th May 2020) - Sun, Dongyang; Mao, Congguang; Du, Chuanbao; Bao, Weimin; Li, Xiaoping
Abstract: When the thin wire whose orientation cannot be parallel to Cartesian axis is modeled by the finite‐difference time‐domain method, the staircasing introduce numerical errors and nonphysical phenomenon. In order to reduce the influence on the induced current, a loaded technique is proposed. The lumped elements are matched at the grid corner based on the contour‐path model. All the electromagnetic difference equations nearby the wire are modified. The accuracy of the proposed technique is demonstrated by the comparison with the method of moment.